Effect of nitrogen fertilizer and weed management on the yield of transplant aman rice (Journal of the Bangladesh Agricultural University, 2018)
The research work was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during aman season from July to December 2015 to study the effect of nitrogen fertilizer and weed management on the growth and yield of transplant aman rice cv. BRRI dhan46. The experiment consisted of four fertilizer treatments viz. 0 kg N ha−1 (N0), 40 kg N ha−1(N1), 80 kg N ha−1(N2) and 120 kg N ha−1(N3) and four weeding treatments viz. one hand weeding at 20 DAT (W1), two hand weedings at 20 and 35 DAT (W2), three hand weedings at 20, 35 and 50 DAT (W3), weeding by Japanese rice weeder twice at 20 and 35 DAT (W4) and unweeded control (W5). The experiment was laid out in the randomized complete block design with three replications. The highest plant height (113.00 cm), number of total tillers hill−1 (8.74), number of effective tillers hill−1 (6.18), panicle length (21.98 cm), number of grains panicle−1 (114.20), grain yield (4.00 t ha−1), straw yield (5.25 t ha−1) and biological yield (9.25 t ha−1) were recorded in N2 (80 kg N ha−1) treatment. The lowest plant height (106.00 cm), number of total tillers hill-1 (7.20), number of effective tillers hill−1 (5.00), panicle length (20.70 cm), number of grains panicle−1 (97.60), grain yield (3.52 t ha−1), straw yield (4.46 t ha−1) and biological yield (7.97 t ha−1) were recorded from N0 (No nitrogen fertilizer control) treatment. On the other hand, the highest grain yield 4.23 t ha−1 was observed in three weedings condition because of the highest number of effective tillers hill−1 (6.81), number of grains panicle−1(111.10). The highest straw yield (5.51 t ha−1) was also found in three weeding condition. The lowest grain yield (3.40 t ha−1) was recorded in W5 (unweeded control) treatment. The lowest straw yield (4.31 t ha−1) was also observed in W5 (unweeded control) treatment because of the smallest plant (106.97 cm) and lower number of total tillers hill−1 (7.20). Therefore, 80 kg N ha−1along with three hand weedings at 20, 35 and 50 DAT may be used for obtaining the highest grain and straw yields of BRRI dhan46J. Bangladesh Agril. Univ. 16(1): 12-16, April 2018